Divine Law in Canon 22 of the Code of Canon Law - Tomasz Gałkowski (Acta Universitatis Lodziensis Folia Iuridica)
Civil law norms may operate in the Church’s legal order. Canon law refers to them as a general norm expressed in canon 22 of the Code of Canon Law. This phenomenon is referred to as the canonisation of civil law. The studies concerning this topic focus on the issues of the concept of canonisation and the technique of its application or practical problems arising from the general norm. The study addresses issues concerning the use of the reference to the divine law in canon 22 and its influence on the interpretation of the norm, the influence of the canonical norm on the understanding of the divine law, and the necessity of its citation in the text of the canon. The author believes that the subject of the just canonical norm (norma iusta) should be added to the existing considerations in canonical doctrine.